Driving factors of growth evidence in the food and textile sectors of Pakistan - Zahid Bashir; Muhammad Usman Arshad; Muhammad Asif; Nusrat Khalid (Financial Internet Quarterly, 2020)
The aim of this research was determining the factors of growth in the textile and food sector of Pakistan. The research study analyzed data from the financial statements of textile and food sector companies of Pakistan for the period 2013-17. A fixed effect regression model was used for regression analysis after the conformation of (Hausman, 1970) specification test. The results of the study indicated that there was a significant and positive impact of profitability and negative impact of leverage on firm growth in textiles as well as the food sector of Pakistan. The results also indicated that firm growth was not significantly affected by innovation, liquidity or solvency. Growth of assets was used to measure firm growth. The findings of the study are applicable to textile as well as food sector companies in Pakistan. This research study suggested that management and policymakers in the textile as well as in the food sector of Pakistan should consider profitability as a driving factor for enhancing growth in both sectors. The present research study contributed to the existing literature by providing fresh evidence from Pakistan as a developing market.
Keywords: C1; C4; C5; C8; G32; L2; L8; M2; 330; Growth; Profitability; Textile & Food sector; Pakistan